Croisement de regards. La phénoménologie de M. Merleau-Ponty et lʼart vidéo de Bill Viola - Matos Dias, Isabel (Daimon Revista Internacional de Filosofia, 2008)
Considering with the last Merleau-Ponty, phenomenology as a philosophical mouvement inspired by a new learning of perception, instead of a completely closed thinking system, Matos Dias reflects about how contemporary video artists keep on this attitude. Analysing specially the films of Bill Viola (his memorable I do not know it is I am like), the portuguese philosopher points on the phenomenological involvement of an artist who is always looking for the specifity of the union of human being and nature, observer and observed.